History of civilizations of central asia -. Vol. 4, pt. 1 Vol. 4 - Asimov, M.S.; Bosworth, Clifford Edmund ([S.l.] : Motilal Banarsidass, 1999)
Volume IV of the History of Civilizations of Central Asia covers some eight centuries during which the new faith of Islam arose affecting over a long period of time, much of Central Asia.